2004
DOI: 10.1016/j.virol.2004.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human immunodeficiency virus type 1 replication by siRNA targeted to the highly conserved primer binding site

Abstract: The initiation of HIV-1 reverse transcription occurs at an 18-nucleotide sequence in the viral genome designated as the primer binding site (PBS), which is complementary to the 3' terminal nucleotides of tRNA(Lys,3). Since the PBS is highly conserved among all infectious HIV-1, it represents an attractive target for the development of new therapeutics to inhibit viral replication. In this study, we have evaluated three approaches using small interfering RNA (siRNAs) targeted to the PBS for the capacity to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…[31][32][33][34] In most previous studies, the targets of siRNAs or shRNAs in HIV-1 transcripts are not in fact highly conserved, and only a few studies focused on targeting conserved HIV-1 sequences. 23,[35][36][37][38] As previously reported 39,40 and our results at 15-18 days postinfection show (Fig. 4A), HIV-1 can escape from inhibition by mutations in sequences targeted by a single shRNA.…”
Section: Discussionsupporting
confidence: 86%
“…[31][32][33][34] In most previous studies, the targets of siRNAs or shRNAs in HIV-1 transcripts are not in fact highly conserved, and only a few studies focused on targeting conserved HIV-1 sequences. 23,[35][36][37][38] As previously reported 39,40 and our results at 15-18 days postinfection show (Fig. 4A), HIV-1 can escape from inhibition by mutations in sequences targeted by a single shRNA.…”
Section: Discussionsupporting
confidence: 86%
“…Unfortunately, long-term studies have shown that prolonged exposure to siRNAs results in mutations of the virus that allow it to escape regulation (6,10). Recently, a study showed that an siRNA targeting the PBS was able to inhibit HIV-1 infection (24). Although no mutation in the PBS was seen up to 14 days after exposure to the siRNA, our studies suggest that HIV can mutate the PBS region to escape targeting by RNAi.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, AAV5 was efficiently transduced into T cells and macrophages ( Fig. 3 and 4), which may be useful for gene therapy of diseases involving hematopoietic cells (4,26,43,57,59,69).…”
Section: Discussionmentioning
confidence: 99%